2017
DOI: 10.1007/s11356-017-0557-2
|View full text |Cite
|
Sign up to set email alerts
|

Devitalisation of pathogens in stored pig slurry and potential risk related to its application to agricultural soil

Abstract: The study investigated the risks arising from application of pig slurry to soil in relation to viability of Salmonella typhimurium, Escherichia coli, total coliforms, faecal enterococci and eggs of Ascaris suum at different temperatures. Potential effect of changes in physico-chemical parameters, particularly dry matter (DM), pH and ammonia, were also investigated. Examination showed that S. typhimurium was devitalised after storage in the slurry for 115 days at 4 °C and after 90 days at 20 and 42 °C. Devitali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 15 publications
2
25
0
2
Order By: Relevance
“…Several authors also reported that fecal shedding is usually sporadic 42,43 and the load can vary from 3 to 50 000 CFU g −1 of feces. As far as Salmonella is concerned, its survival is highly dependent on low temperature and ammonia concentrations, 41 as well as high moisture levels 44 . On the other hand, temperatures of 20–30 °C can quicken the die‐off of these microorganisms 44 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors also reported that fecal shedding is usually sporadic 42,43 and the load can vary from 3 to 50 000 CFU g −1 of feces. As far as Salmonella is concerned, its survival is highly dependent on low temperature and ammonia concentrations, 41 as well as high moisture levels 44 . On the other hand, temperatures of 20–30 °C can quicken the die‐off of these microorganisms 44 .…”
Section: Discussionmentioning
confidence: 99%
“…As far as Salmonella is concerned, its survival is highly dependent on low temperature and ammonia concentrations, 41 as well as high moisture levels 44 . On the other hand, temperatures of 20–30 °C can quicken the die‐off of these microorganisms 44 . Indeed, the ambient temperature in the area where the study was conducted fell in the range of 23–26 °C.…”
Section: Discussionmentioning
confidence: 99%
“…Proper manure management is an important part of the pig farm biosecurity plan (Van Immerseel et al, 2018) as pig manure is known to be an important source of many infectious diseases (swine dysentery, classical swine fever, foot and mouth disease, Salmonella spp., Escherichia coli, etc.) (Venglovsky et al, 2018), including ASF virus . Pathogens can survive or even grow in manure as this substrate provides the necessary nutrients and protects them against UV radiation, desiccation and high temperature.…”
Section: Manurementioning
confidence: 99%
“…Colder temperatures generally allow longer survival times for microorganisms. Besides temperature and time of storage, the survival of pathogens in slurry also depends on other factors such as moisture content, free ammonia concentration, pH, the presence of other microorganisms and other physicochemical properties (Venglovsky et al, 2018). Several studies have shown the presence of ASFV in faeces and urine (Haas et al, 1995;.…”
Section: Manurementioning
confidence: 99%
“…(up to 9 years), Trichuris spp. (up to 11 years), and coccidial oocysts [30,223]. Due to pig excretory behavior, pastures presented an irregular distribution of A. suum eggs with the presence of hot spots.…”
Section: Health Managementmentioning
confidence: 99%